Trade Interaction between India and ASEAN Countries: An Empirical Study - Philip, Abey; Alappatt, Mathew (World Business Institute Australia, 2012)
Using cross sectional data for the year 1980-2010, this paper investigates the importance of relevant macro variable of ASEAN on Indian international trade. It is also important to analyses the significance of different bilateral agreements and its impact on Indian international trade. GATT and WTO have been advocating trade liberalisation and bilateral agreement and aims to promote the free trade among member countries. This paper is trying to look into India’s market led regional interaction among ASEAN countries. The national saving of ASEAN countries and Free trade agreement seems to be influencing the bilateral trade of India. Research shows that Indian bilateral trade is not utilizing enough the growth of ASEAN economy. This paper will help the policy makers to understand how much international trade and involvement in bilateral agreement is helping India to become an important role player in Asia. This study also suggests possible measures and avenues to take advantage of emerging economic opportunities for mutual benefits.